An integrated mainstream and sidestream strategy for overcoming nitrite oxidizing bacteria adaptation in a continuous plug-flow nutrient removal process. (January 2021) - Qiu, Shuang; Wang, Lingfeng; Chen, Zhipeng; Yang, Mingzhu; Yu, Ziwei; Ge, Shijian
Graphic abstract: Highlights: Nitritation was achieved in a continuous plug-flow A/O process treating sewage. Integrated alternating mainstream aeration and sidestream treatments was applied. Alternate FNA/FA sludge treatment every three days overcame NOB adaptation. Aerobic sludge should be taken for sidestream treatment to avoid anoxic starvation. ALASF ensured denitrification and created anoxic disturbance for NOB inhibition. Abstract: An integrated mainstream aeration and sidestream sludge treatment was demonstrated to be effective in overcoming the adaptation of nitrite oxidizing bacteria (NOB) in an anoxic/oxic process. Results showed that by employing the alternating free nitrous acid and free ammonia (FNA/FA) sidestream sludge treatment alone, nitritation was established but varied, which was addressed by integrating alternating aeration with step feeding (ALASF) in reactor. Two critical considerations contributed to stable effluent nitrite accumulation (>83.8 %) and nitrogen removal (>83.0 %): 1)  aerobic sludge rather than return sludge should be taken for FNA/FA treatment to avoid anoxic starvation which facilitated NOB recovery; 2) ALASF ensured timely denitritation and created constant anoxic disturbance for NOB inhibition. Nitrospira and Nitrobacter after 540-day operation were 0.38 % of seed sludge. A 20 % reduction of operating cost was obtained in this nitritation process. This study moved  nitritation one step closer to application in continuous plug-flow process from municipal wastewater.